Salvage Versus Adjuvant Radiation Treatment for Women With Early-Stage Endometrial Carcinoma: A Matched Analysis. Issue 2 (1st February 2016) - Vance, Sean; Burmeister, Charlotte; Rasool, Nabila; Buekers, Thomas; Elshaikh, Mohamed A.
Abstract : Objectives: Adjuvant radiation treatment (ART) has been shown to reduce local recurrences in early-stage endometrial carcinoma (EC); however, this has not translated into improved overall survival (OS) benefit. As a result, some physicians forgo ART, citing successful salvage rates in cases of recurrence. Survival end points were compared between women treated with salvage RT (SRT) for locoregional recurrence and similarly matched women treated upfront with ART. Materials and Methods: We identified 40 patients with stage I to II type 1 EC who underwent hysterectomy and received no adjuvant RT but later developed locoregional recurrence and subsequently received SRT. An additional 374 patients who underwent hysterectomy followed by ART during the same period were identified. Patients in the SRT group were matched to those in the ART group based on FIGO (International Federation of Gynecology and Obstetrics) stage and tumor grade in a 1:3 ratio. Disease-specific survival (DSS) and OS were calculated. Results: A total of 156 women were matched (39:117). Median follow-up was 56 months. The 2 groups were generally well balanced. With regard to the site of tumor recurrence, it was commonly vaginal in the SRT group (74.3% vs 28.6%, P = 0.01). More SRT patients received a combination of pelvic external-beam RT with vaginal brachytherapy (94.8% vs 35%, P < 0.001). The ART group had significantly better 5-year DSS (95% vs 77%, P < 0.001) and 5-year OS (79% vs 72%, P = 0.005) compared with those of the SRT group. Conclusions: Our study suggests that women who receive SRT for their locoregional recurrence have worse DSS and OS compared with those matched patients who received ART. Further studies are warranted to develop a high-quality cost-effectiveness analysis as well as accurate predictive models of tumor recurrence. Until then, ART should at least be considered in the management of early-stage EC patients with adverse prognostic factors.